7
$\begingroup$

How do you sum this series? $$\sum _{y=1}^m \frac{y}{(m-y)!(m+y)!}$$

My attempt:

$$\frac{y}{(m-y)!(m+y)!}=\frac{y}{(2m)!}{2m\choose m+y}$$

My thoughts were, sum this from zero, get a trivial answer, take away the first term. But actually I don't think this will work very well.

This question was originally under probability, but the problem is that I can't sum a series and really has nothing to do with probability (reason for the first comment)

$\endgroup$
2
  • $\begingroup$ What are positive paths? I can't identify any common features of the paths in the image. $\endgroup$ – joriki May 2 '13 at 10:24
  • $\begingroup$ Each move we get $S_k=S_{k-1}\pm 1$, I want $\min_{1\leq k \leq n} S_k>0$, so all of the lines which stay strictly above the x-axis. $\endgroup$ – shilov May 2 '13 at 10:32
6
+100
$\begingroup$

For example, one can write

\begin{align} \sum_{y=0}^m\frac{y}{(m-y)!(m+y)!} &= \sum_{k=0}^m\frac{m-k}{k!(2m-k)!} \\ &=\frac{m}{(2m)!}\sum_{k=0}^m{2m \choose k}-\frac{1}{(2m-1)!}\sum_{k=1}^{m}{2m-1\choose k-1} \\ &= \frac{m}{2(2m)!}\left[{2m\choose m}+\sum_{k=0}^{2m}{2m \choose k}\right]-\frac{1}{(2m-1)!}\sum_{k=0}^{m-1}{2m-1\choose k} \\ &= \frac{m}{2(2m)!}\left[{2m\choose m}+\left(1+1\right)^{2m}\right]-\frac{1}{2(2m-1)!}\sum_{k=0}^{2m-1}{2m-1\choose k} \\ &= \frac{m}{2(2m)!}{2m\choose m}+\frac{m\cdot 2^{2m}}{2(2m)!}-\frac{2^{2m-1}}{2(2m-1)!} \\ &= \frac{m}{2(2m)!}{2m\choose m}\;. \end{align} All we have used in the way is that $\displaystyle{n\choose k} ={n\choose n-k}$ and that $\displaystyle(1+1)^n=\sum_{k=0}^n{n\choose k}$.

$\endgroup$
3
  • $\begingroup$ I took the liberty of arranging the equations in somewhat more orderly fashion :-) $\endgroup$ – joriki May 5 '13 at 20:34
  • $\begingroup$ Could you clarify how you obtained the first equality? $\endgroup$ – Spine Feast May 5 '13 at 20:39
  • 1
    $\begingroup$ @DepeHb: The first equality comes from a change of summation index: $y=m-k$. $\endgroup$ – Start wearing purple May 7 '13 at 21:08
3
$\begingroup$

Try maxima on this. Load zeilberger, and:

GosperSum(y * binomial(2 m, m + y), y, 1, m)

gives $$\dfrac{1}{2}(m + 1) \binom{2 m}{m + 1}$$

$\endgroup$
1
  • $\begingroup$ Hi, I used Mathematica to sum it, but I want to know how the technique $\endgroup$ – shilov May 3 '13 at 16:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.